Agronomic and Quality Traits of 30 Eggplant Germplasm Resources from China - Jian Lyu; Li Jin; Xianglan Ma; Yansu Li; Mintao Sun; Ning Jin; Shuya Wang; Linli Hu; Jihua Yu (Plants, 2025)
(1) Background: Eggplant is a widely grown, high-value vegetable crop whose commercial demand has increased in recent years owing to its unique nutritional features. Variations in its agronomic and nutritional traits are of great importance in the selection of eggplant varieties. (2) Methods: In this study, 30 different eggplant varieties were evaluated concerning the morphological characteristics and nutritional value of their fruits. (3) Results: Among the eight morphological characteristics evaluated, the coefficient of variation was highest for fruit calyx thorns, pericarp brightness, and fruit shape index. The diversity index (H’) for pulp color was the largest, followed by pericarp brightness, but was the smallest for fruit weight. Principal component analysis showed that the morphological characteristics contributed 73.20% for the observed diversity among the 30 eggplant varieties, whereas eggplant fruit quality traits had a minor effect. Of note, significant differences in the soluble protein, vitamin C, nitrate, soluble sugar, organic acid, and mineral contents was observed within the samples, with organic acids, vitamin C, and hardness contributing more to the total variation observed. Multiple sets of correlations among the indices were found, with significant positive correlations between transverse diameter and hardness, fruit weight and fruit shape index, as well as between malic acid, fructose, and sucrose; (4) Conclusions: Altogether, these findings may help create breeding strategies to promote the selection of superior genotypes and help guide future germplasm collection.